Phage therapy for extensively drug resistant Acinetobacter baumannii infection: case report and in vivo evaluation of the distribution of phage and the impact on gut microbiome - Qu, Jiayao; Zou, Jin; Zhang, Jiancong; Qu, Jiuxin; Lu, Hongzhou (Frontiers in Medicine, 2024)
Numerous studies have documented successful instances of bacteriophage therapy in treating infections caused by extensively drug-resistant Acinetobacter baumannii (XDRAB). However, the safety profile of phage therapy and its effects on the human gut microbiota remain areas of concern. In this study, we collected blood, sputum, and fecal samples from an elderly female patient during two phases of inhaled bacteriophage therapy targeting extensively drug-resistant Acinetobacter baumannii (XDRAB). We investigated the in vivo distribution of bacteriophages and their impact on the gut microbiome. Bacteriophage DNA was detected in blood samples exclusively during the first 4 days of the second phase of phage therapy, with Ct values ranging from 32.6 to 35.3. In sputum samples, the Ct values of phages demonstrated a decreasing trend from 45 to 14.7 during the first phase of phage therapy, subsequently stabilizing between 28.5 and 26.8 in the second phase. In fecal samples, a significant reduction in the Ct value of phages was observed following both phases of bacteriophage treatment, with values decreasing from 35.5 to 22.5 and from 32.6 to 22.7, respectively. The composition of the gut microbiota was analyzed using Illumina-based 16S rRNA sequencing from fecal samples. Sequencing analysis revealed significant alterations in the microbiota composition at both the phylum and genus levels during phage therapy. These findings suggest that inhaled phages are detectable in human blood and tend to accumulate in the intestines. Furthermore, notable changes in the gut microbiota were observed throughout the duration of the phage treatment.